2017
DOI: 10.1038/s41598-017-15886-5
|View full text |Cite
|
Sign up to set email alerts
|

Partial loss-of-function of NAL1 alters canopy photosynthesis by changing the contribution of upper and lower canopy leaves in rice

Abstract: Little is known about the genetic basis of leaf and canopy photosynthesis. Here we aimed to detect novel quantitative trait loci (QTL) controlling photosynthesis by increasing leaf nitrogen content (LNC) per leaf area and analysed its effect on leaf and canopy photosynthesis. To identify QTL that increase photosynthetic rate in leaves, we screened chromosome segment substitution lines (CSSLs) of Oryza sativa ssp. japonica cultivar Koshihikari and O. sativa ssp. indica cultivar Nona Bokra using LNC per leaf are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This has previously been suggested for soybeans (Soleh et al, 2016a). Although several genetic factors affecting A sat have already been detected (Adachi et al, 2011(Adachi et al, , 2017Hirotsu et al, 2017;Takai et al, 2013), there is no information on the genetic factors regulating the induction response. Genetic methods, such as QTL analysis or GWAS (genome wide association study), use data from a large number of rice varieties in their analyses.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This has previously been suggested for soybeans (Soleh et al, 2016a). Although several genetic factors affecting A sat have already been detected (Adachi et al, 2011(Adachi et al, , 2017Hirotsu et al, 2017;Takai et al, 2013), there is no information on the genetic factors regulating the induction response. Genetic methods, such as QTL analysis or GWAS (genome wide association study), use data from a large number of rice varieties in their analyses.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, we previously reported that there is a significant genetic diversity in photosynthetic capacity in rice (Kanemura et al, 2007). Quantitative trait loci (QTLs) and candidate genes have been identified, which improve photosynthetic capacity in rice (Adachi et al, 2011(Adachi et al, , 2017Hirotsu et al, 2017;Takai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, putative QTLs have been detected for Single-Photon Avalanche Diode (SPAD) value, chlorophyll content, stomatal conductance, sink size, source strength, carbon isotope discrimination, and carbohydrate translocation ( Ulloa et al, 2000 ; Teng et al, 2004 ; Takai et al, 2010 , 2013 ). Potential QTLs have been revealed also for net CO 2 assimilation rate (A n ) in rice ( Ishimaru et al, 2001 ; Price et al, 2002 ; Zhao et al, 2011 ; Hirotsu et al, 2017 ; Ye et al, 2017 ; Adachi et al, 2019 ), barley ( Teulat et al, 2002 ; Cantalapiedra et al, 2015 ; Liu et al, 2017 ; Du et al, 2019 ), maize ( Fracheboud et al, 2002 ), soybean ( Jun et al, 2014 ; Lv et al, 2018 ; Liu D. et al, 2019 ), cucumber ( Zhang et al, 2004 ), and legumes ( Muchero et al, 2009 ; Kumar et al, 2014 ; Li F. et al, 2015 ). In the case of rice, several loci enhancing leaf A n have been detected on chromosomes 3, 4, 5, 6, 8, 9, and 11 ( Adachi et al, 2011 ; Gu et al, 2012 ).…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
“…Here, we aimed at collecting the data on temporal changes in canopy photosynthesis of Koshihikari and Takanari over the entire growing season by using the MIC-100 to analyse its association with crop growth rate (CGR) and total biomass accumulation. We assumed that photosynthesis in the uppermost fully expanded leaf is representative of canopy photosynthesis, since it has the highest photosynthetic capacity and receives the strongest radiation in the canopy 43 , 46 , 55 . We also observed ontogenic changes of chlorophyll content (SPAD value) and single leaf area (single LA).…”
Section: Introductionmentioning
confidence: 99%